Ergonomic intervention on a packing workstation with robotic aid-case study at a furniture manufacturing industry - Colim, Ana S. (2020)
BACKGROUND: Several risk factors among packing lines workers can lead to Work-related Musculoskeletal Disorders (WRMSD) occurrence. Foreseeing WRMSD prevention and productivity increase, some furniture manufacturing industries have been investing in the adoption of robotic solutions. In this field, ergonomics plays an important role to verify if automation implementation has been successful. OBJECTIVE: This study aims to address the general impact and effectiveness from an ergonomics point of view of the implementation of a robotic aid in a packing workstation. METHODS: The Nordic Musculoskeletal Questionnaire (NMQ) was applied to 14 workers of semi-automated packing lines. Some additional questions about occupational conditions were included. In order to assess the ergonomic impact of the robotic aid, Rapid Upper Limb Assessment (RULA) was also applied by trained ergonomists, by analyzing the considered packing workstations before and after the adoption of the robotic aid proposed solution. RESULTS: The results showed that trunk torsion was the most highlighted WRMSD risk factor by all workers, associating it with the lumbar pain. The obtained RULA scores demonstrated that the adoption of a robotic aid eliminated this risk factor and, consequently, reduced the corresponding WRMSD risk. CONCLUSIONS: The adoption of robotic aids can be instrumental in reducing WRMSD risk in furniture manufacturing industries. Ergonomic studies with workers' participatory approaches seem to be an appropriate strategy to enable the validation and development of industrial robotic solutions.